Optimasi Formula Gel Buah Apel Hijau (Pyrus malus L.) sebagai Antioksidan dengan Kombinasi Basis Carbopol 940 dan Gliserin secara Simplex Lattice Design - Prayoga Fery Yuniarto; Endang Sri Rejeki; Dewi Ekowati (Jurnal Farmasi Indonesia, 2014)
Apple is suspected has an antioxidant. The use of apple fruit directly considered less practical, so that it made the gel preparations. This research was aimed to optimation by Simplex Lattice Design method to get the most optimum formula gel of apple fruit as antioxidant gel. The apple fruit was macerated. The apple fruit gel use carbopol 940 (C) and glycerin (G) with three formula, F1 (100%C), F2 (50%C: 50%G), dan F3 (100%G). Optimation gel was done based on viscosity, adhesion, and dispersive power by Simplex Lattice Design method with design- expert 8.0.6.1 program. The optimum gel was analyzed the antioxidant activity by DPPH method by probit analysis for calculate IC50 value and vitamin C was used as control. The study shown that optimum combination of carbopol 940 and gliserin as basis was carbopol 2.448 g and glycerin 2.552 g. The optimum gel of apple fruit had antioxidant activity (IC50 151,43 ppm). Storage time affected the viscosity of the gel which tends to decrease during the months of storage.